Alloimmunization to transfused platelets requires priming of CD4(+) T cells in the splenic microenvironment in a murine model - Gilson, Christopher R (2011)
BACKGROUND: Alloantibodies are a clinically significant sequelae of platelet transfusion, potentially rendering patients refractory to ongoing platelet transfusion support. These antibodies are often IgG class switched, suggesting the involvement of CD4(+) T cell help; however, platelet specific CD4(+) T cells have not been visualized in vivo and specifics of their stimulation are not completely understood. STUDY DESIGN AND METHODS: A murine model of alloimmunization to transfused platelets was developed to allow in vivo assessment and characterization of CD4(+) T cells specific for platelet MHC alloantigen. Platelets were harvested from BALB/c mice, filter leukoreduced, and transfused into C57BL/6 recipients. Platelet specific CD4(+) T cell responses were visualized by using a TCR transgenic mouse that detects peptide from donor MHC I presented on recipient MHC II. Antibody responses were determined by indirect immunofluorescence using BALB/c donor targets. RESULTS: C57BL/6 recipients of BALB/c leukoreduced platelet transfusions produced anti-BALB/c antibodies, with proliferation of antigen specific CD4(+) T cells seen in the spleen but not lymph nodes or liver. Depletion of recipient CD4(+) cells or splenectomy independently abrogated the alloantibody response. CONCLUSION: We report a novel model to study antigen-specific CD4(+) T cells during alloimmunization to platelet transfusion. The presented data support a critical role for CD4(+) T cell help in the humoral response to platelet transfusion and establish the spleen as a required microenvironment for effective CD4(+) T cell priming against donor platelet derived MHC I.